2023
DOI: 10.1371/journal.pone.0291981
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic combination of doxorubicin with hydralazine, and disulfiram against MCF-7 breast cancer cell line

Zainab Lafi,
Walhan Alshaer,
Lobna Gharaibeh
et al.

Abstract: Disulfiram and hydralazine have recently been reported to have anti-cancer action, and repositioned to be used as adjuvant in cancer therapy. Chemotherapy combined with other medications, such as those that affect the immune system or epigenetic cell profile, can overcome resistance with fewer adverse effects compared to chemotherapy alone. In the present study, a combination of doxorubicin (DOX) with hydrazine (Hyd) and disulfiram (Dis), as a triple treatment, was evaluated against wild-type and DOX-resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 65 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…It spatially instigated the lysosomal and late endosomal disorganization [31]. Another study revealed that triple treatment with DSF, doxorubicin (DOX), and hydrazine (Hyd) sensitizes both DOX-resistant MCF-7 cells and their wild-type counterparts by inducing apoptosis [32]. Remarkably, DSF decreased the required dose of DOX to induce cytotoxicity in DOX-resistant cells.…”
Section: Sensitization Of Drug-resistant Bc Cells By Anti-alcoholic D...mentioning
confidence: 99%
“…It spatially instigated the lysosomal and late endosomal disorganization [31]. Another study revealed that triple treatment with DSF, doxorubicin (DOX), and hydrazine (Hyd) sensitizes both DOX-resistant MCF-7 cells and their wild-type counterparts by inducing apoptosis [32]. Remarkably, DSF decreased the required dose of DOX to induce cytotoxicity in DOX-resistant cells.…”
Section: Sensitization Of Drug-resistant Bc Cells By Anti-alcoholic D...mentioning
confidence: 99%